2000
DOI: 10.1136/bmj.320.7240.985
|View full text |Cite
|
Sign up to set email alerts
|

Measuring brain natriuretic peptide in suspected left ventricular systolic dysfunction in general practice: cross-sectional study

Abstract: The prevalence of heart failure is increasing.1 Patients usually present to their general practitioner but a definitive diagnosis of left ventricular systolic dysfunction can only be achieved by cardiac imaging. Measuring plasma concentrations of brain natriuretic peptide has been advocated as a screening test that might reduce demands on cardiological services. 2 We report the results of a community based study designed to investigate the effectiveness of measuring brain natriuretic peptide to diagnose lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 3 publications
1
42
1
Order By: Relevance
“…The prevalence of heart failure was 28.7%, which is similar to comparable previous studies. 25,26,31,32 The use of a loop diuretic was a predictor of the presence of heart failure in our study, which seems somewhat surprising as its prescription is often related to heart failure, but is understandable from a clinical point of view. Patients presenting with symptoms of volume overload will often be treated with loop diuretics to alleviate symptoms, usually before tests to confirm heart failure are performed.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The prevalence of heart failure was 28.7%, which is similar to comparable previous studies. 25,26,31,32 The use of a loop diuretic was a predictor of the presence of heart failure in our study, which seems somewhat surprising as its prescription is often related to heart failure, but is understandable from a clinical point of view. Patients presenting with symptoms of volume overload will often be treated with loop diuretics to alleviate symptoms, usually before tests to confirm heart failure are performed.…”
Section: Discussionmentioning
confidence: 70%
“…Three other studies of similar patients comparing BNP with other readily available diagnostic tests concluded that BNP is the most powerful diagnostic test. 25,26,32 The vast majority of other studies assessing the diagnostic value of NT-proBNP were, however, performed in hospital emergency rooms and not in an outpatient or primary care setting. It should be emphasized that univariable diagnostic characteristics, such as sensitivity and specificity, cannot be routinely generalized from 1 setting to another.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent finding of all reports is the excellent negative predictive value of BNP. Furthermore, BNP has a good negative likelihood ratio for diagnosis of LVD compared with standard clinical indices, such as clinical history, electrocardiogram, and chest x-ray (17 ). These clinical results led to the development of numerous commercially available assays to determine different natriuretic peptide hormones (18 ).…”
mentioning
confidence: 99%
“…The absence of statistically significant differences in BNP levels in these groups may be accounted for by the well-known stimulating effect of low EF on BNP release [14, 15, 18, 19]. This mechanism outweighs the impact of asynchrony on the increase in BNP, which is already high in the presence of reduced EF.…”
Section: Discussionmentioning
confidence: 90%